CHANGING TRENDS OF MULTIDRUG RESISTANT BACTERIA: A SIX YEAR EXPERIENCE FROM A TERTIARY CARE HOSPITAL - Adnan, Fareeha; Khursheed, Nazia; Khan, Maira; Maria Mushtaq Ali,; Shakir Hussain,; Neelum mansoor, (Journal of Ayub Medical College Abbottabad, 2022)
Background: There is a continuous increase in the number of bacteria showing resistance to various antibiotics, limiting the treatment options for infections. The objective of this study was to assess the trend in resistance pattern of multi drug resistant organisms over a period of 6 years. Methods: A retrospective study was conducted in Indus Hospital and Health Network, Karachi, Pakistan from January 2014 to December 2019. Multidrug resistant organisms were isolated from various samples and the data of corresponding patients were extracted from electronic medical record. The patients of all age groups and either gender was included. Specimens were inoculated on Sheep Blood Agar, chocolate agar and MacConkey agar. Organisms were identified and antibiotic susceptibility testing was performed according to Clinical Laboratory Standard Institute guidelines. Results: In 34628 cases, 5159 (14.8%) were isolated as MDR organisms. Out of these 44.2% were Gram negative, while 55.7% were Gram-positive bacteria. The highest MDR trend was observed for A. baumannii (0-70%) followed by MRSA (0-64%) P. aeruginosa (0-16%) Enterococcus (0-10%) CRE (2.8-5.8%). Conclusion: The continuous rising trend of multidrug resistant organisms has been observed during the period of our study. Therefore, there is an imperative need of constant monitoring and firm adherences to infection control strategies to avoid spread of MDR organisms.